2023
DOI: 10.1155/2023/3427026
|View full text |Cite
|
Sign up to set email alerts
|

Topical Calcipotriol for the Treatment of Cutaneous Warts: An Assessor‐Blind Randomized Placebo‐Controlled Trial

Abstract: Background. Cutaneous warts are common epidermal proliferations caused by human papillomavirus (HPV). We aimed to determine the safety and efficacy of topical calcipotriol for the treatment of cutaneous warts. Methods. This assessor-blind randomized placebo-controlled trial included 56 patients with cutaneous warts referred to a dermatology clinic from January 21 to March 20, 2020. Patients were randomized into two groups (n = 28). One group received calcipotriol 0.05% ointment twice a day on the lesions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Moreover, the calcipotriol group exhibited a significantly higher rate of complete response to treatment. 40 Another study with 42 patients experiencing multiple cutaneous warts demonstrated a complete response in 78.8 percent of patients treated with intralesional vitamin D3. 41 In a study involving 64 patients with recurrent warts, injections of 0.2-0.5 mL at a concentration of 15 mg/ mL were administered at 3-week intervals.…”
Section: Vitamin D and Verrucamentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the calcipotriol group exhibited a significantly higher rate of complete response to treatment. 40 Another study with 42 patients experiencing multiple cutaneous warts demonstrated a complete response in 78.8 percent of patients treated with intralesional vitamin D3. 41 In a study involving 64 patients with recurrent warts, injections of 0.2-0.5 mL at a concentration of 15 mg/ mL were administered at 3-week intervals.…”
Section: Vitamin D and Verrucamentioning
confidence: 98%
“…39 Intralesional vitamin have proven to be both safe and effective, while only a limited number of studies have indicated the effectiveness of applying vitamin D derivatives topically. 40 Imagawa and Suzuki initially achieved success in treating refractory warts in 17 patients using topical vitamin D3 (maxacalcitol). For all of the patients, the warts disappeared.…”
Section: Vitamin D and Verrucamentioning
confidence: 99%